Selenium Nanoparticles Synthesized by Ball Milling Method: Their Characterization to Incorporate in Poultry Feed - Bharathi, Arun; Valavan, S. Ezhil; Veeramani, P.; Chitra, M. Ananda; Ramesh, J.; Churchill, R. Richard (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted in April, 2023 at Madras Veterinary College, Chennai, India to study the efficiency of nanoselenium in alleviating heat stress in broilers. To incorporate nana Se in poultry diet, the selenium nanoparticles were synthesized by the ball milling technique (physical method) using feed-grade sodium selenite powder at 250 rpm in a planetary ball mill. The result showed that the product yield of synthesized nano selenium as 95.04% after milling for five hour thirty minutes. The dynamic light scattering technique was used to analyse the particle size and zeta potential of nano Se, which resulted in 69.1 nm and –23.9, respectively. The X-ray Diffraction revealed that the selenium nanoparticle was crystalline in nature. The Fourier Transform Infra-Red Spectroscopy analysis displayed the characteristic peaks at 3437, 2923 and 2851, 1601, 1427 corresponding to the presence of O-H, C-H, C=O, COO- functional groups, respectively which show the stability of synthesized nano selenium. The well-defined peak in the FTIR spectrum confirmed that there were no impurities in the synthesized nano Se. The transmission electron microscope unveiled the size of nano Se in the range of 6–20 nm and the shape of synthesized nano Se was spherical in nature. Hence, it can be concluded that the nano selenium synthesized productively through a physical method and can be utilized as a mineral supplement in the commercial poultry diet.